Process characteristics and interfacial microstructure in spot impact welding of titanium to stainless steel. (February 2020) - Li, Jianxiong; Schneiderman, Benjamin; Gilbert, S. Michelle; Vivek, Anupam; Yu, Zhenzhen; Daehn, Glenn
Abstract: Vaporizing foil actuator (VFA) spot welding was used to weld a titanium alloy (Ti-1.2ASN) to a stainless steel (436 SS) for the first time. The relation of process to microstructure was explored. Interfacial microstructure was studied through optical microscopy (OM), scanning electron microscopy (SEM), and transmission electron microscopy (TEM). Chemical compositions of molten regions and jet zone were characterized by energy-dispersive X-ray spectroscopy (EDS). The microhardness across the interface was measured through Vickers and nanoindentation tests. The results show that an impact velocity of 800 m/s can be achieved at very low input energy. VFA spot welds present heterogeneity in microstructure at large and small length scales. At long length scales, several regions of weld can be seen. At the center there is no bonding; moving radially outward the collision angle increases from zero and this causes a transition from a flat area with considerable melting to a wavy region, and finally an area of accumulated jetted material in the corner. EDS analyses show that discontinuous intermetallics including TiCr2, Fe2 Ti and FeTi, and Ti fragments coexisted in a mixed zone that probably has components of mechanical and liquid-state mixing. TEM results show that equiaxed nanograins exhibited in the recrystallization zone and mixed zone. There is an 'impact affected zone' near the interface where the hardness rises significantly. At the edges of the weld there is a mixed, and oxidized zone that supports the idea that solid-state impact jets the nascent surfaces away to allow interatomic bonding.